Development of Chemistry LKPD Based on TPACK Using the Problem Based Learning (PBL) Model on Hydrocarbon Topics - Sirait, Martina; Simatupang, Patricia; Simanjuntak, Evalina Br; Tambunan, Kristine; Manalu, Elisabet; Sianturi, Irianani Ainung; Pulungan, Ahmad Nasir (Universitas Lampung, 2024)
The purpose of this study to develop TPACK-based LKPD using PBL model to see the extent to which the use of LKPD and practicum can improve student learning outcomes on hydrocarbon materials. The research method used is Research & Development (R & D) with 4D models (define, design, develop and desseminate) with a limited trial. On liveworksheet assisted e-LKPD conducted feasibility validation test and praktiklaitas test by 2 teachers chemistry and 27 learners. The result is an interactive e-LKPD with almost the same characteristics as the printed LKPD, based on everyday phenomena and equipped with video shows. Based on expert validation, the percentage of material aspects, learning, e-LKPD validation, and e-LKPD validation by education practitioners were 97.9%, 100℅, 95% and 81.25%, respectively. The percentage of student response in the field trial was 93.22% with problem solving skills of 86.92%.Keywords: Hydrocarbons, Worksheet Learners, Technological Pedagogical and Content Knowledge, Problem Based Learning Model.DOI: 10.23960/jppk.v13.i3.32146